Model Matematika Dinamika Perilaku Bullying dengan Intervensi Sekolah dan Resiliensi Siswa - Ilmi, Noraniza Bahrotul; Muniroh, Muna Afdi; Hastari, Ratri Candra; Prasetya, Nizarkasyi Fighar (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
In this study, a model of bullying behavior transmission was developed by incorporating school interventions and student resilience. Finding the equilibrium point, figuring out the basic reproduction number , and assesing the equilibrium point’s stability are all part of dynamical analysis. Two equilibrium points are identified, namely the bullying-free equilibrium and the bullying-present equilibrium.. The dynamical analysis result shows that the bullying- free equilibrium point is locally asymtotically stable if , conversely, when  the bullying-present equilibrium point is locally asymtotically stable. The numerical simulations result are consistent with the analytical result.